Anisotropic bonded samarium-iron-nitrogen permanent magnet and preparation method thereof

By oriented the magnetic field and external force on the roller, anisotropic samarium-nitrogen permanent magnet is formed, which solves the problem of insufficient magnetic performance of samarium-nitrogen permanent magnet, significantly improves magnetic performance and meets the needs of high-performance applications.

CN119324101APending Publication Date: 2025-01-17ANHUI UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411437601.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The magnetic properties of existing samarium-ferro-nitrogen permanent magnets are insufficient, especially the maximum magnetic energy content of isotropic samarium-ferro-nitrogen magnets is generally less than 10MGOe, which is difficult to meet the needs of high-performance applications.

Method used

Hexagonal crystal samarium-iron nitrogen magnetic powder is used to combine with thermoplastic resin, and anisotropic samarium-iron nitrogen permanent magnet is formed by oriented magnetic field and external force on the roller. The easy magnetization axis of samarium-iron nitrogen particles is arranged in the magnetic field to improve magnetic performance.

Benefits of technology

It significantly improves the residual magnetism, intrinsic coercive force and maximum magnetic energy product of anisotropic samarium-nitrogen permanent magnet, reaching 6.5-10KGs, 10-15KOe and 10-15MGOe, meeting the new high-performance application needs and expanding the application scope .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324101A_ABST
    Figure CN119324101A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rare earth permanent magnets, and particularly discloses an anisotropic bonded samarium-iron-nitrogen permanent magnet and a preparation method thereof, and the anisotropic bonded samarium-iron-nitrogen permanent magnet is mainly composed of samarium-iron-nitrogen magnetic powder and a binder; wherein the samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder; the binder is thermoplastic resin; the anisotropic bonded samarium-iron-nitrogen permanent magnet has good magnetic performance, and the method for preparing the anisotropic bonded samarium-iron-nitrogen permanent magnet comprises the steps that stress orientation is conducted on the samarium-iron-nitrogen magnetic powder, meanwhile, the permanent magnet is adopted on a roller to conduct magnetic field orientation on the samarium-iron-nitrogen magnetic powder, the anisotropic samarium-iron-nitrogen permanent magnet is obtained, and the magnetic performance is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnets, and in particular to an anisotropic bonded samarium iron nitride permanent magnet and a preparation method thereof. Background Art

[0002] SmFeN is a new type of rare earth permanent magnet material with high magnetic properties, high cost performance, high Curie temperature and strong corrosion resistance. It can be widely used in the manufacture of motors, generators, sensors, etc. The high magnetic properties and high Curie temperature of SmFeN play an important role in improving energy utilization efficiency, reducing energy loss, and reducing the volume of equipment. It has broad application prospects and growth space in the domestic and foreign markets. However, SmFeN magnetic powder has encountered significant challenges in the manufacture of sintered magnets. Due to the poor thermal stability of SmFeN magnetic powder and its easy decomposition and phase change at high temperatures, it is difficult to prepare high-performance sintered permanent magnets like traditional rare earth magnets (such as NdFeB and SmCo). Bonded SmFeN magnets can be prepared at lower temperatures, will not cause SmFeN decomposition and oxidation, and can prepare magnets with complex shapes and high precision. Therefore, SmFeN magnetic powder magnets show significant superiority in the preparation of bonded magnets.

[0003] As the requirements for lightweight, high efficiency and low cost of devices increase in application scenarios, the high remanence, high coercivity, high magnetic energy product and high Curie temperature of bonded SmFeN magnets show obvious competitive advantages. Most SmFeN permanent magnet products on the market are isotropic, and their maximum magnetic energy product is generally lower than 10MGOe, which limits their application.

[0004] Invention patent JP3840893B2, bonded magnet and its manufacturing method, this method uses reduction diffusion method to prepare samarium iron nitrogen magnetic powder, crushes and mixes the magnetic powder and resin at the same time, and then presses them to obtain isotropic samarium iron nitrogen bonded magnet, which is difficult to meet high performance requirements. Invention patent CN102568736A, a rigid anisotropic bonded NdFeB permanent magnet, this method mixes NdFeB magnetic powder and resin in a certain proportion, granulates them through a co-directional meshing twin-screw extruder, adds the granules to a single-screw extruder, and uses the extruder for mechanical orientation to obtain magnets of different specifications, which has low stress orientation and poor effect. Invention patent CN102360653A, a calendered anisotropic flexible rare earth bonded magnet and its manufacturing method, the method mixes anisotropic rare earth composite permanent magnet powder, adhesive and processing aid evenly and then crushes them, and calenders them by a double roller machine, thereby improving the magnetic properties of the bonded magnet, but only adopts the stress field orientation of calendering double roller pressing. Invention patent CN114023551A, an anisotropic rubber composite rare earth permanent magnet orientation forming process, after heating and softening rare earth permanent magnet powder (including samarium iron nitrogen magnetic powder, neodymium iron boron magnetic powder and neodymium iron nitrogen magnetic powder) and rubber granules, connect the electromagnet to generate a 1.5T electromagnetic field, the upper and lower magnetic poles of the magnetic head are N and S poles respectively, and the heated material is neatly arranged according to the direction of the magnetic field when passing through the die with a magnetic field, achieving orientation, and improving the magnetic properties of the flexible rubber composite rare earth permanent magnet, but the magnetic field is generated by the electromagnet, which consumes energy, has a complex structure and high cost. Invention patent CN109786098A, a method for preparing a flexible rubber NdFeB magnet with a high filling ratio, NdFeB powder is added to an organic solution containing a silane coupling agent and an epoxy resin to obtain surface-modified NdFeB powder, and then the surface-modified NdFeB powder, rubber binder, and auxiliary materials are evenly mixed and kneaded to obtain rubber NdFeB granules, the obtained rubber NdFeB granules are molded to obtain a semi-finished product, the obtained semi-finished product is cut, and magnetized along the thickness direction at a voltage of 800-1500V to improve the magnetic properties of the NdFeB magnet. Summary of the invention

[0005] The purpose of the present invention is to meet the demand for anisotropic SmFeN high-performance permanent magnets in new application scenarios, thereby providing an anisotropic bonded SmFeN permanent magnet and a preparation method thereof. The anisotropic bonded SmFeN permanent magnet has good magnetic properties, and the method for preparing the anisotropic bonded SmFeN permanent magnet is to perform magnetic field orientation on the SmFeN magnetic powder using a permanent magnet on a roller while performing stress orientation on the SmFeN magnetic powder, so as to obtain an anisotropic SmFeN permanent magnet, which significantly improves the magnetic properties.

[0006] In order to achieve the above-mentioned object, in the first aspect, the present invention provides an anisotropic bonded SmFeN permanent magnet, which is mainly composed of SmFeN magnetic powder and a binder; wherein,

[0007] The samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder;

[0008] The binder is a thermoplastic resin.

[0009] Preferably, the preparation method of the hexagonal SmFeN magnetic powder comprises: using rare earth samarium and iron ingot as raw materials, mixing and smelting, and spinning to obtain SmFe castings; heat treating the SmFe castings, and then jet milling to obtain SmFe powder; and nitriding the SmFe powder.

[0010] Preferably, according to Sm2Fe 17 The rare earth samarium and the iron ingot are proportioned according to the stoichiometric ratio of the samarium element and the iron element.

[0011] More preferably, the mixed smelting conditions include: under vacuum conditions, a temperature of 1350-1450° C., and a time of 5-20 min.

[0012] Further preferably, the heat treatment conditions include: temperature of 1000-1050° C. and time of 2-4 h.

[0013] More preferably, the conditions of the air flow mill include: crushing and grinding the samarium iron castings with a crusher in the presence of nitrogen.

[0014] More preferably, the nitriding conditions include: nitriding the samarium iron powder for 10-24 hours at a temperature of 450-550° C. under a nitrogen or ammonia atmosphere.

[0015] Preferably, the thermoplastic resin is selected from one or more of polyamide, polyphenylene ether, polyphenylene sulfide and polyamide-imide.

[0016] Preferably, the anisotropic bonded SmFeN permanent magnet further comprises a surfactant and a mixed plastic additive.

[0017] More preferably, the mixed plastic additives include a lubricant and an antioxidant.

[0018] More preferably, the surfactant is one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent.

[0019] More preferably, the lubricant is paraffin and / or polyethylene wax.

[0020] More preferably, the antioxidant is a phenol antioxidant and / or a phosphate antioxidant.

[0021] Preferably, the mass percentage of the samarium iron nitrogen magnetic powder is 70-95wt%.

[0022] Preferably, the mass percentage of the surfactant is 0.25-5wt%.

[0023] More preferably, the mass percentage of the thermoplastic resin is 5-25wt%.

[0024] Further preferably, the mass percentage of the mixed plastic additive is 1-5wt%.

[0025] In a second aspect, the present invention provides a method for preparing an anisotropic bonded SmFeN permanent magnet, the method comprising: firstly treating the surface of SmFeN magnetic powder with a surfactant, then adding a binder and a mixed plastic additive to obtain a mixture, and pressing and molding; wherein,

[0026] The samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder;

[0027] The binder is a thermoplastic resin;

[0028] The compression molding is to calender and orient the mixture through a double-roll machine equipped with permanent magnets.

[0029] Preferably, the preparation method of the hexagonal SmFeN magnetic powder comprises: using rare earth samarium and iron ingot as raw materials, mixing and smelting, and spinning to obtain SmFe castings; heat treating the SmFe castings, and then jet milling to obtain SmFe powder; and nitriding the SmFe powder.

[0030] Preferably, according to Sm2Fe 17 The rare earth samarium and the iron ingot are proportioned according to the stoichiometric ratio of the samarium element and the iron element.

[0031] More preferably, the mixed smelting conditions include: under vacuum conditions, at a temperature of 1350-1450° C., and for 5-20 min.

[0032] Further preferably, the heat treatment conditions include: temperature of 1000-1050° C. and time of 2-4 h.

[0033] More preferably, the conditions of the air flow mill include: crushing and grinding the samarium iron castings with a crusher in the presence of nitrogen.

[0034] More preferably, the nitriding conditions include: nitriding the samarium iron powder for 10-24 hours at a temperature of 450-550° C. under a nitrogen or ammonia atmosphere.

[0035] Preferably, the thermoplastic resin is selected from one or more of polyamide, polyphenylene ether, polyphenylene sulfide and polyamide-imide.

[0036] Preferably, the anisotropic bonded SmFeN permanent magnet further comprises a surfactant and a mixed plastic additive.

[0037] More preferably, the mixed plastic additives include a lubricant and an antioxidant.

[0038] More preferably, the surfactant is one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent.

[0039] More preferably, the lubricant is paraffin and / or polyethylene wax.

[0040] More preferably, the antioxidant is a phenol antioxidant and / or a phosphate antioxidant.

[0041] Preferably, in the anisotropic bonded SmFeN permanent magnet, the mass percentage of the SmFeN magnetic powder is 70-95wt%.

[0042] Preferably, the mass percentage of the surfactant is 0.25-5wt%.

[0043] More preferably, the mass percentage of the thermoplastic resin is 5-25wt%.

[0044] Further preferably, the mass percentage of the mixed plastic additive is 1-5wt%.

[0045] More preferably, the mass percentage of the lubricant in the mixed plastic additive is 0.1-2%, and the mass percentage of the antioxidant is 0.1-2%.

[0046] Preferably, the surface treatment conditions include: a stirring rate of 10-20 rpm and a time of 10-30 min.

[0047] Preferably, the surface layer of the rollers of the roller machine is made of non-magnetic steel.

[0048] Preferably, the grade of the non-magnetic steel is 50Mn18Cr4WN or HPM75.

[0049] More preferably, the permanent magnet is selected from magnetized NdFeB permanent ferrite and / or SmCo permanent ferrite.

[0050] Further preferably, the surface magnetism of the permanent magnet is 0.7-1.5T.

[0051] More preferably, the roller diameter of the double roller mill is 500-1000 mm, and the roller length is 1200-1800 mm.

[0052] More preferably, the driving motor power of the roller machine is 1.5-10kw, and the roller speed is 5-35rpm.

[0053] In the above technical scheme, the anisotropic bonded SmFeN permanent magnet of the present invention is mainly composed of hexagonal SmFeN magnetic powder and thermoplastic resin, wherein the shape-anisotropic hexagonal SmFeN magnetic powder, under the action of magnetic field and external force, makes the SmFeN grains parallel to the C-axis and stacked, that is, stacked in hexagonal sheets perpendicular to the pressure direction, and the orientation effect is good, thereby obtaining anisotropic bonded SmFeN permanent magnet with excellent magnetic properties.

[0054] At the same time, since the C axis of the SmFeN particles is the easy magnetization axis, the orientation effect of the grains in the magnetic field can be arranged in the direction of the magnetic field. A permanent magnet is installed on the surface of the roller to form a magnetic field. The C axis of the SmFeN particles is arranged along the magnetic field under the action of the magnetic field, which can increase the orientation degree of the anisotropic hexagonal SmFeN magnetic powder and further improve the magnetic properties of the flat-plate rolled anisotropic SmFeN magnet. The present invention orients the SmFeN magnetic powder by simultaneously orienting the SmFeN magnetic powder by the magnetic field on the surface of the roller and mechanical stress, thereby achieving the orientation of the SmFeN magnetic powder perpendicular to the C axis and preparing an anisotropic bonded SmFeN permanent magnet. The remanence (B r ) reached 6.5-10KGs, the intrinsic coercivity H cj Reached 10-15KOe, maximum magnetic energy product (BH) max It has reached 10-15MGOe, which significantly improves the magnetic properties, meets the demand for anisotropic bonded SmFeN permanent magnets in new application scenarios, and expands the application scope of anisotropic bonded SmFeN permanent magnets.

[0055] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0057] Figure 1 This is a result diagram of magnetic property testing of finished magnets obtained in the embodiments and comparative examples of the present invention in Test Example 1;

[0058] Figure 2 is the XRD pattern of the samarium iron casting sheet in Preparation Example 1 of the present invention;

[0059] Figure 3 is the XRD pattern of the samarium iron nitrogen powder in Preparation Example 1 of the present invention;

[0060] Figure 4 is a SEM image of the samarium iron casting sheet in Preparation Example 1 of the present invention when the scale length is 1 μm;

[0061] Figure 5is a SEM image of the samarium iron casting sheet in Preparation Example 1 of the present invention when the scale length is 500 nm;

[0062] Figure 6 is a SEM image of the samarium iron casting sheet in Preparation Example 1 of the present invention when the scale length is 500 nm;

[0063] Figure 7 is a SEM image of the samarium iron casting sheet in Preparation Example 1 of the present invention when the scale length is 300 nm;

[0064] Figure 8 is a SEM image of the samarium iron nitrogen powder in Preparation Example 1 of the present invention when the scale length is 2 μm;

[0065] Fig. 9 is a SEM image of the rolled magnetic field oriented samarium iron nitride permanent magnet in Example 1 of the present invention when the scale length is 20 μm;

[0066] Fig.10 is a SEM image of the rolled magnetic field oriented samarium iron nitride permanent magnet in Comparative Example 1 of the present invention when the scale length is 10 μm;

[0067] Fig.11 It is a schematic diagram of the preparation of the anisotropic bonded SmFeN permanent magnet of the present invention. DETAILED DESCRIPTION

[0068] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0069] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0070] In a first aspect, the present invention provides an anisotropic bonded SmFeN permanent magnet, which is mainly composed of SmFeN magnetic powder and a binder; wherein:

[0071] The samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder;

[0072] The binder is a thermoplastic resin.

[0073] The anisotropic bonded SmFeN permanent magnet of the invention mainly consists of hexagonal SmFeN magnetic powder and thermoplastic resin, wherein the SmFeN crystal grains are distributed in parallel layers along the C axis under the action of magnetic field and external force, that is, they are stacked in hexagonal sheets perpendicular to the pressure direction, and the orientation effect is good, thereby obtaining the anisotropic bonded SmFeN permanent magnet with excellent magnetic properties.

[0074] In a preferred embodiment of the present invention, in order to achieve a good orientation effect, the preparation method of the hexagonal samarium iron nitrogen magnetic powder includes: using rare earth samarium and iron ingot as raw materials, mixing and smelting, and spinning to obtain samarium iron castings; heat treating the samarium iron castings, and then jet milling to obtain samarium iron powder; and nitriding the samarium iron powder.

[0075] In a preferred embodiment of the present invention, in order to obtain the desired samarium iron alloy, according to Sm2Fe 17 The stoichiometric ratio of the samarium element and the iron element in the formula is used to mix the rare earth samarium and the iron ingot. Since the samarium element is easily volatile, 20% (mass percentage) more samarium is added on the basis of the calculated amount as compensation.

[0076] In a preferred embodiment of the present invention, in order to prevent excessive volatilization of samarium, the mixed smelting conditions include: under vacuum conditions, a temperature of 1350-1450° C., and a time of 5-20 min.

[0077] In a preferred embodiment of the present invention, in order to eliminate the α-Fe impurity phase, the Sm2Fe 17 The heat treatment conditions include: temperature of 1000-1050°C and time of 2-4h.

[0078] In a preferred embodiment of the present invention, in order to refine the samarium iron alloy and facilitate nitriding treatment, the conditions of the air flow mill include: crushing and grinding the samarium iron casting with a crusher in the presence of nitrogen.

[0079] In a preferred embodiment of the present invention, in order to improve the magnetocrystalline anisotropy, the nitriding conditions include: nitriding the samarium iron powder for 10-24 hours at a temperature of 450-550° C. in a nitrogen or ammonia atmosphere.

[0080] In a preferred embodiment of the present invention, in order to increase the bonding degree between SmFeN magnetic powder particles and give SmFeN magnet mechanical properties, the thermoplastic resin is selected from one or more of polyamide, polyphenylene ether, polyphenylene sulfide and polyamide-imide.

[0081] In a preferred embodiment of the present invention, in order to improve the performance of the SmFeN magnet, the anisotropic bonded SmFeN permanent magnet further comprises a surfactant and a mixed plastic additive.

[0082] In a preferred embodiment of the present invention, in order to reduce the wear and oxidation of the SmFeN magnetic powder during processing, thereby improving the performance of the SmFeN magnet, the mixed plastic additive includes a lubricant and an antioxidant.

[0083] In a preferred embodiment of the present invention, in order to better bond the magnetic powder, the surfactant is one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent.

[0084] In a preferred embodiment of the present invention, in order to reduce the wear of the SmFeN magnetic powder during processing, the lubricant is paraffin and / or polyethylene wax.

[0085] In a preferred embodiment of the present invention, in order to reduce the oxidation of the SmFeN magnetic powder during processing, the antioxidant is a phenol antioxidant and / or a phosphate antioxidant.

[0086] In a preferred embodiment of the present invention, in order to give full play to the magnetic properties of SmFeN, in the anisotropic bonded SmFeN permanent magnet, the mass percentage of the SmFeN magnetic powder is 70-95wt%.

[0087] In a preferred embodiment of the present invention, in order to better bind the magnetic powder, the mass percentage of the surfactant is 0.25-5wt%.

[0088] In a preferred embodiment of the present invention, in order to better increase the bonding degree between the SmFeN magnetic powder particles and give the SmFeN magnet mechanical properties, the mass percentage of the thermoplastic resin is 5-25wt%.

[0089] In a preferred embodiment of the present invention, in order to better improve the performance of the samarium iron nitrogen magnet, the mass percentage of the mixed plastic additive is 1-5wt%.

[0090] In a preferred embodiment of the present invention, in order to better reduce the wear and oxidation of the SmFeN magnetic powder during processing, thereby improving the performance of the SmFeN magnet, the mass percentage of the lubricant in the mixed plastic additive is 0.1-2%, and the mass percentage of the antioxidant is 0.1-2%.

[0091] In a second aspect, the present invention provides a method for preparing an anisotropic bonded SmFeN permanent magnet, the method comprising: firstly treating the surface of SmFeN magnetic powder with a surfactant, then adding a binder and a mixed plastic additive to obtain a mixture, and pressing and molding; wherein,

[0092] The samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder;

[0093] The binder is a thermoplastic resin;

[0094] The compression molding is to calender and orient the mixture through a double-roll machine equipped with permanent magnets.

[0095] The present invention orients the SmFeN magnetic powder simultaneously by means of the magnetic field and mechanical stress on the roller surface, thereby achieving the orientation of the SmFeN magnetic powder perpendicular to the C axis, and preparing an anisotropic bonded SmFeN permanent magnet. The anisotropic bonded SmFeN permanent magnet manufactured by the present invention has a remanence (Br) of 6.5-10KGs, an intrinsic coercive force Hcj of 10-15KOe, and a maximum magnetic energy product (BH)max of 10-15MGOe, which significantly improves the magnetic properties, meets the demand for anisotropic bonded SmFeN permanent magnets in new application scenarios, and expands the application range of the anisotropic bonded SmFeN permanent magnet.

[0096] In a preferred embodiment of the present invention, the preparation method of the hexagonal samarium iron nitrogen magnetic powder includes: using rare earth samarium and iron ingot as raw materials, mixing and smelting, and spinning to obtain samarium iron castings; heat treating the samarium iron castings, and then jet milling to obtain samarium iron powder; and nitriding the samarium iron powder.

[0097] In a preferred embodiment of the present invention, in order to control the purity of the product, according to Sm2Fe 17 The rare earth samarium and the iron ingot are proportioned according to the stoichiometric ratio of the samarium element and the iron element.

[0098] In a preferred embodiment of the present invention, in order to avoid oxidation of samarium iron and obtain a uniform alloy phase, the mixed smelting conditions include: under vacuum conditions, a temperature of 1350-1450° C., and a time of 5-20 min.

[0099] In a preferred embodiment of the present invention, in order to eliminate the α-Fe impurity phase, the Sm2Fe 17 The heat treatment conditions include: temperature of 1000-1050°C and time of 2-4h.

[0100] In a preferred embodiment of the present invention, in order to eliminate the α-Fe impurity phase, the Sm2Fe 17 The heat treatment conditions include: temperature of 1000-1050°C and time of 2-4h.

[0101] In a preferred embodiment of the present invention, in order to refine the samarium iron alloy and facilitate nitriding treatment, the conditions of the air flow mill include: crushing and grinding the samarium iron casting with a crusher in the presence of nitrogen.

[0102] In a preferred embodiment of the present invention, in order to improve the magnetocrystalline anisotropy, the nitriding conditions include: nitriding the samarium iron powder for 10-24 hours at a temperature of 450-550° C. in a nitrogen or ammonia atmosphere.

[0103] In a preferred embodiment of the present invention, in order to increase the bonding degree between SmFeN magnetic powder particles and give SmFeN magnet mechanical properties, the thermoplastic resin is selected from one or more of polyamide, polyphenylene ether, polyphenylene sulfide and polyamide-imide.

[0104] In a preferred embodiment of the present invention, in order to improve the performance of the SmFeN magnet, the anisotropic bonded SmFeN permanent magnet further comprises a surfactant and a mixed plastic additive.

[0105] In a preferred embodiment of the present invention, in order to reduce the wear and oxidation of the SmFeN magnetic powder during processing, thereby improving the performance of the SmFeN magnet, the mixed plastic additive includes a lubricant and an antioxidant.

[0106] In a preferred embodiment of the present invention, in order to better bond the magnetic powder, the surfactant is one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent.

[0107] In a preferred embodiment of the present invention, in order to reduce the wear of the SmFeN magnetic powder during processing, the lubricant is paraffin and / or polyethylene wax.

[0108] In a preferred embodiment of the present invention, in order to reduce the oxidation of the SmFeN magnetic powder during processing, the antioxidant is a phenol antioxidant and / or a phosphate antioxidant.

[0109] In a preferred embodiment of the present invention, in order to give full play to the magnetic properties of SmFeN, in the anisotropic bonded SmFeN permanent magnet, the mass percentage of the SmFeN magnetic powder is 70-95wt%.

[0110] In a preferred embodiment of the present invention, in order to better bind the magnetic powder, the mass percentage of the surfactant is 0.25-5wt%.

[0111] In a preferred embodiment of the present invention, in order to better increase the bonding degree between the SmFeN magnetic powder particles and give the SmFeN magnet mechanical properties, the mass percentage of the thermoplastic resin is 5-25wt%.

[0112] In a preferred embodiment of the present invention, in order to better improve the performance of the samarium iron nitrogen magnet, the mass percentage of the mixed plastic additive is 1-5wt%.

[0113] In a preferred embodiment of the present invention, in order to better reduce the wear and oxidation of the SmFeN magnetic powder during processing, thereby improving the performance of the SmFeN magnet, the mass percentage of the lubricant in the mixed plastic additive is 0.1-2%, and the mass percentage of the antioxidant is 0.1-2%.

[0114] In a preferred embodiment of the present invention, in order to better bond the magnet, the surface treatment conditions include: a stirring rate of 10-20 rpm and a time of 10-30 min.

[0115] In a preferred embodiment of the present invention, in order to reduce magnetic leakage and control the magnetic induction intensity on the surface of the rollers, the surface layer of the rollers of the roller machine is made of non-magnetic steel.

[0116] In a preferred embodiment of the present invention, in order to improve the wear resistance of the roller surface, the grade of the non-magnetic steel is 50Mn18Cr4WN or HPM75.

[0117] In a preferred embodiment of the present invention, in order to form a magnetic field on the surface of the roller pair, the permanent magnet is selected from magnetized neodymium iron boron permanent ferrite and / or samarium cobalt permanent ferrite.

[0118] In a preferred embodiment of the present invention, in order to fully orient the C-axis of the SmFeN particles along the magnetic field under the action of the magnetic field, the surface magnetism of the permanent magnet is 0.7-1.5T.

[0119] In a preferred embodiment of the present invention, in order to better calender the magnet, the cylinder diameter of the double-roller machine is 500-1000 mm, and the cylinder length is 1200-1800 mm.

[0120] In a preferred embodiment of the present invention, in order to more fully calender the magnet, the driving motor power of the roller machine is 1.5-10kw, and the rotating speed of the rollers is 5-35rpm.

[0121] The present invention will be described in detail below through examples. In the following examples, the drugs and pharmaceutical agents are all conventional commercial products.

[0122] Preparation Example 1

[0123] (1) Using rare earth samarium with a purity of 99.9% and iron ingot with a purity of 99.9% as raw materials, according to Sm2Fe 17 The stoichiometric ratio of samarium and iron is such that 20% more is added to the calculated amount of samarium as compensation because samarium is easily volatile.

[0124] (2) Mix the weighed rare earth samarium and iron ingot raw materials, add them into a crucible of a vacuum melting furnace, evacuate to 8 Pa, melt at a temperature of 1420° C. for 10 min, and then spin them into sheets in a rapid quenching furnace to obtain samarium iron casting sheets;

[0125] (3) The samarium iron casting sheet is heat treated at a temperature of 1050°C for 3 hours, and then placed in a crusher and filled with nitrogen for air flow mill crushing. The speed of the air flow mill is 2800 r / min to obtain samarium iron powder with a particle size of 1-10 μm. The samarium iron casting sheet is nitrided in a tubular furnace under a nitrogen atmosphere at a temperature of 470°C for 10 hours to obtain samarium iron nitrogen powder with a particle size of 1-10 μm.

[0126] Example 1

[0127] (1) Weighing the materials according to 92% by mass of the samarium iron nitrogen powder prepared in Preparation Example 1, 7% by mass of thermoplastic resin polyphenylene sulfide (PPS), 0.25% by mass of a titanate coupling agent, 0.5% by mass of an antioxidant butylated hydroxytoluene (BHT), and 0.25% by mass of a lubricant wax liquid;

[0128] (2) dissolving the weighed titanate coupling agent in an appropriate amount of acetone to obtain a mixed surface treatment agent (the amount of acetone is limited to that which can completely cover the magnetic powder), and then adding the weighed samarium iron nitrogen magnetic powder of Preparation Example 1, stirring well and drying for 6 hours to obtain surface-treated samarium iron nitrogen magnetic powder;

[0129] (3) The weighed PPS, BHT and lubricant wax liquid are mixed with the surface-treated SmFeN magnetic powder obtained in step (2) to obtain a mixture, and the heated and softened mixture is subjected to a first rolling forming process using a double-roller mill equipped with a permanent magnet to obtain a thin flat rolled magnet, wherein the roller speed ratio of the front and rear rollers of the double-roller mill is 1:1, and the roller spacing is 0.5 mm; the thin flat anisotropic SmFeN rolled magnet is stacked and rolled again, while the roller speed ratio of the front and rear rollers of the double-roller mill is maintained at 1:1, and the roller spacing is adjusted to obtain an anisotropic bonded SmFeN permanent magnet, which is recorded as B1.

[0130] Example 2

[0131] The method of Example 1 is followed, except that the mass percentages of the materials in step (1) are replaced by 93% of the samarium iron nitrogen powder obtained in Preparation Example 1, 6% of the thermoplastic resin polyphenylene sulfide (PPS), 0.5% of the titanate coupling agent, 0.25% of the antioxidant butylated hydroxytoluene (BHT) and 0.25% of the lubricant wax liquid to obtain an anisotropic bonded samarium iron nitrogen permanent magnet, denoted as B2.

[0132] Example 3

[0133] The method of Example 1 is followed, except that the mass percentage and type of each material in step (1) are replaced by 92% of the samarium iron nitride powder obtained in Preparation Example 1, 7% of the thermoplastic resin polyetherimide (PAI2), 0.5% of the titanate coupling agent, 0.25% of the antioxidant butylated hydroxytoluene (BHT) and 0.25% of the lubricant wax liquid to obtain an anisotropic bonded samarium iron nitride permanent magnet, which is denoted as B3.

[0134] Example 4

[0135] The method of Example 1 is followed, except that the mass percentage and type of each material in step (1) are replaced by 93% of the samarium iron nitride powder prepared in Preparation Example 1, 6% of the thermoplastic resin polyetherimide (PAI2), 0.5% of the titanate coupling agent, 0.25% of the antioxidant butylated hydroxytoluene (BHT) and 0.25% of the lubricant wax liquid to obtain an anisotropic bonded samarium iron nitride permanent magnet, which is denoted as B4.

[0136] Comparative Example 1

[0137] The method of Example 1 is followed, except that in step (3), no permanent magnet is added to the roller mill to obtain a samarium iron nitrogen magnet, which is denoted as D1.

[0138] Comparative Example 2

[0139] The method of Example 3 was followed, except that no permanent magnet was added to the roller mill, and a samarium iron nitrogen magnet was obtained, which was recorded as D2.

[0140] Comparative Example 3

[0141] The method of Example 1 is followed, except that in step (3), the mixture after heating and softening is directly molded by a mold to obtain a samarium iron nitrogen magnet, which is denoted as D3.

[0142] Comparative Example 4

[0143] The method of Example 3 was followed, except that the mixture after heating and softening was directly molded by a mold to obtain a samarium iron nitrogen magnet, which was recorded as D4.

[0144] Test Example 1

[0145] The magnetic properties of the finished magnets prepared in the above Examples 1-2, 4 and Comparative Examples 1 and 3 were tested using a vibrating sample magnetometer (VSM). The specific results are as follows: Figure 1 shown.

[0146] pass Figure 1It can be seen that the hexagonal SmFeN magnetic powder in Examples 1-2 and 4 of the present invention is subjected to the shear force of the rollers, so that the SmFeN grains are distributed in parallel layers along the C axis, and the obtained anisotropic bonded SmFeN permanent magnets have improved magnetic properties compared with the SmFeN magnets obtained by the traditional molding method in Comparative Examples 1 and 3.

[0147] Test Example 2

[0148] The samarium iron castings and samarium iron nitrogen powder in Preparation Example 1 were analyzed by X-ray diffractometer (XRD). Figure 2-3 .

[0149] Depend on Figure 2 It can be seen that the XRD spectrum of the samarium iron casting obtained in Preparation Example 1 is similar to that of the standard Sm2Fe 17 The characteristic diffraction peak position of the sample is consistent with that of the sample, indicating that the method of the present invention is used to obtain Sm2Fe 17 Casting Figure 3 It can be seen that the XRD spectrum of the samarium iron nitrogen powder obtained in Preparation Example 1 is similar to that of the standard Sm2Fe 17 The characteristic diffraction peak position of N3 is consistent, indicating that Sm2Fe 17 N3 powder.

[0150] Test Example 3

[0151] The morphologies of the samarium iron casting sheet, samarium iron nitrogen powder in Preparation Example 1, the rolled magnetic field oriented samarium iron nitrogen permanent magnet in Example 1, and the rolled samarium iron nitrogen permanent magnet in Comparative Example 1 were characterized using a scanning electron microscope. The results are as follows: Figure 4-10 shown.

[0152] Depend on Figure 4-7 The SEM image shows that the samarium iron casting obtained in Preparation Example 1 has a distinct hexagonal structure. Figure 2 The XRD diagram shows that the method of the present invention can obtain a Sm2Fe 17 Casting sheet.

[0153] Depend on Figure 8 From the scanning electron microscope image, it can be seen that the samarium iron nitrogen powder with a particle size of 1-10 μm was obtained by air jet milling in Preparation Example 1.

[0154] Depend on Fig. 9 It can be seen from the scanning electron microscope image that under the action of external force, the anisotropic hexagonal SmFeN magnetic powder in Example 1 causes the SmFeN grains to be stacked parallel to the C axis, that is, stacked in hexagonal sheets perpendicular to the pressure direction.

[0155] Depend on Fig.10 It can be seen from the scanning electron microscope image that the parallel stacking distribution effect of the samarium iron nitrogen magnetic powder only subjected to calendering orientation in Comparative Example 1 is obviously poor.

[0156] Test Example 4

[0157] The magnetic properties of the finished magnets obtained in the above Examples 1-4 and Comparative Examples 1-4 were tested, and the specific test results are shown in Table 1:

[0158] Table 1

[0159]

[0160] From the above content and the data in Table 1, it can be seen that under the action of the shear force of the roller, the SmFeN magnetic powder makes the SmFeN grains parallel to the C axis and the obtained anisotropic bonded SmFeN permanent magnet has improved magnetic properties compared with the SmFeN magnets obtained by the traditional molding method; the C axis of the SmFeN particles is the easy magnetization axis. By utilizing the orientation effect that the grains can be arranged in the direction of the magnetic field in the magnetic field, the permanent magnet is added to the surface of the roller to form a magnetic field. The C axis of the SmFeN particles is arranged along the magnetic field under the action of the magnetic field, which can increase the orientation degree of the anisotropic hexagonal SmFeN magnetic powder and further improve the magnetic properties of the flat-shaped rolled anisotropic SmFeN magnet. In addition, the magnetic properties of the SmFeN magnet using PAI2 as a binder are better than PPS.

[0161] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0162] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0163] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An anisotropic bonded samarium iron nitride permanent magnet, characterized in that: The anisotropic bonded SmFeN permanent magnet is mainly composed of SmFeN magnetic powder and a binder; wherein, The samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder; The binder is a thermoplastic resin.

2. The anisotropic bonded SmFeN permanent magnet according to claim 1, characterized in that: The preparation method of the hexagonal crystal samarium iron nitrogen magnetic powder comprises: using rare earth samarium and iron ingot as raw materials, mixing and smelting, and spinning to obtain samarium iron castings; heat treating the samarium iron castings, and then jet milling to obtain samarium iron powder; nitriding the samarium iron powder; Preferably, according to Sm2Fe 17 According to the stoichiometric ratio of the samarium element and the iron element in the mixture, the rare earth samarium and the iron ingot are proportioned; More preferably, the mixed smelting conditions include: under vacuum conditions, a temperature of 1350-1450° C., and a time of 5-20 min; Further preferably, the heat treatment conditions include: temperature of 1000-1050°C and time of 2-4h; More preferably, the conditions of the jet mill include: crushing and grinding the samarium iron casting sheet with a crusher in the presence of nitrogen; More preferably, the nitriding conditions include: nitriding the samarium iron powder for 10-24 hours at a temperature of 450-550° C. under a nitrogen or ammonia atmosphere.

3. The anisotropic bonded SmFeN permanent magnet according to claim 1 or 2, characterized in that: The thermoplastic resin is selected from one or more of polyamide, polyphenylene ether, polyphenylene sulfide and polyamide-imide; Preferably, the anisotropic bonded SmFeN permanent magnet further comprises a surfactant and a mixed plastic additive; More preferably, the mixed plastic additives include a lubricant and an antioxidant; Further preferably, the surfactant is selected from one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent; More preferably, the lubricant is paraffin and / or polyethylene wax; More preferably, the antioxidant is a phenol antioxidant and / or a phosphate antioxidant.

4. The anisotropic bonded SmFeN permanent magnet according to any one of claims 1 to 3, characterized in that: The mass percentage of the samarium iron nitrogen magnetic powder is 70-95wt%; Preferably, the mass percentage of the surfactant is 0.25-5wt%; More preferably, the mass percentage of the thermoplastic resin is 5-25wt%; Further preferably, the mass percentage of the mixed plastic additive is 1-5wt%.

5. A method for preparing anisotropic bonded samarium iron nitride permanent magnets, characterized in that: The preparation method comprises: firstly treating the surface of samarium iron nitrogen magnetic powder with a surfactant, then adding a binder and a mixed plastic additive to obtain a mixture, and pressing and molding; wherein, The samarium iron nitrogen magnetic powder is hexagonal crystal samarium iron nitrogen magnetic powder; The binder is a thermoplastic resin; The compression molding is to calender and orient the mixture through a double-roll machine equipped with permanent magnets.

6. The preparation method according to claim 5, characterized in that: The preparation method of the hexagonal crystal samarium iron nitrogen magnetic powder comprises: using rare earth samarium and iron ingot as raw materials, mixing and smelting, and spinning to obtain samarium iron castings; heat treating the samarium iron castings, and then jet milling to obtain samarium iron powder; nitriding the samarium iron powder; Preferably, according to Sm2Fe 17 According to the stoichiometric ratio of the samarium element and the iron element in the mixture, the rare earth samarium and the iron ingot are proportioned; More preferably, the mixed smelting conditions include: under vacuum conditions, a temperature of 1350-1450° C., and a time of 5-20 min; Further preferably, the heat treatment conditions include: temperature of 1000-1050°C and time of 2-4h; More preferably, the conditions of the jet mill include: crushing and grinding the samarium iron casting sheet with a crusher in the presence of nitrogen; More preferably, the nitriding conditions include: nitriding the samarium iron powder for 10-24 hours at a temperature of 450-550° C. under a nitrogen or ammonia atmosphere.

7. The preparation method according to claim 5 or 6, characterized in that: The thermoplastic resin is selected from one or more of polyamide, polyphenylene ether, polyphenylene sulfide and polyamide-imide; Preferably, the anisotropic bonded SmFeN permanent magnet further comprises a surfactant and a mixed plastic additive; More preferably, the mixed plastic additives include a lubricant and an antioxidant; Further preferably, the surfactant is one or more of a titanate coupling agent, a silane coupling agent and an aluminate coupling agent; More preferably, the lubricant is paraffin and / or polyethylene wax; More preferably, the antioxidant is a phenol antioxidant and / or a phosphate antioxidant.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In the anisotropic bonded SmFeN permanent magnet, the mass percentage of the SmFeN magnetic powder is 70-95wt%; Preferably, the mass percentage of the surfactant is 0.25-5wt%; More preferably, the mass percentage of the thermoplastic resin is 5-25wt%; Further preferably, the mass percentage of the mixed plastic additive is 1-5wt%; More preferably, the mass percentage of the lubricant in the mixed plastic additive is 0.1-2%, and the mass percentage of the antioxidant is 0.1-2%.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The surface treatment conditions include: a stirring rate of 10-20 rpm and a time of 10-30 min.

10. The preparation method according to any one of claims 5 to 9, characterized in that: The surface layer of the rollers of the roller machine is made of non-magnetic steel; Preferably, the grade of the non-magnetic steel is 50Mn18Cr4WN or HPM75; More preferably, the permanent magnet is selected from magnetized NdFeB permanent magnet ferrite and / or SmCo permanent magnet ferrite; Further preferably, the surface magnetism of the permanent magnet is 0.7-1.5T; More preferably, the cylinder diameter of the roller mill is 500-1000 mm, and the cylinder length is 1200-1800 mm; More preferably, the driving motor power of the roller machine is 1.5-10kw, and the roller speed is 5-35rpm.

Citation Information

Patent Citations

  • Flexible rare earth bonded magnet with roll anisotropy and manufacturing method thereof

    CN102360653A

  • Rigid anisotropy bonded neodymium iron boron permanent magnet

    CN102568736A

  • Preparation method for flexible rubber neodymium iron boron magnet with high filling ratio

    CN109786098A

  • Orientation forming process of anisotropic rubber composite rare earth permanent magnet

    CN114023551A

  • Bonded magnet manufacturing method and bonded magnet

    JP3840893B2